EXPLORING FACTORS INFLUENCING USERS’ INTENSTION TOWARDS CONTINUED USE OF CURRENT FITNESS APPLICATIONS IN THE CONTEXT OF SAUDI ARABIA - Alsultan, Wala (2019)
This dissertation focuses on the factors that influence Saudi users’ continuous usage decisions with respect to the context of fitness apps. In this empirical study, the online questionnaire is used for data collecting. First, this study reviews existing literature as the theoretical foundation to formulate the research hypotheses and construct the model based on Expectation Confirmation Model (ECM). After that, a result is obtained by analyzing the collected data via the online questionnaire. According to the path analysis results, among the six variables chosen, satisfaction, perceived enjoyment, and trust were found to have a significant direct influence on the continued use of fitness apps among Saudi users. The perceived usefulness and perceived ease of use had indirect effects on intentions to keep using fitness apps. Four mediation roles have been examined. The conclusion in the fitness apps domain has a significant value for who is interested in such results in the fitness apps continuous use areas including apps developers, governments, and scholars.